Comparing docosahexaenoic acid (DHA) concomitant with neoadjuvant chemotherapy versus neoadjuvant chemotherapy alone in the treatment of breast cancer (DHA WIN): protocol of a double-blind, phase II, randomised controlled trial. Issue 9 (17th September 2019) - Newell, Marnie; Mackey, John R; Bigras, Gilbert; Alvarez-Camacho, Mirey; Goruk, Susan; Ghosh, Sunita; Schmidt, Alison; Miede, Deborah; Chisotti, Ann; Postovit, Lynne; Baker, Kristi; Mazurak, Vera; et al.
Abstract : Introduction: Neoadjuvant chemotherapy for breast cancer treatment is prescribed to facilitate surgery and provide confirmation of drug-sensitive disease, and the achievement of pathological complete response (pCR) predicts improved long-term outcomes. Docosahexaenoic acid (DHA) has been shown to reduce tumour growth in preclinical models when combined with chemotherapy and is known to beneficially modulate systemic immune function. The purpose of this trial is to investigate the benefit of DHA supplementation in combination with neoadjuvant chemotherapy in patients with breast cancer. Methods and analysis: This is a double-blind, phase II, randomised controlled trial of 52 women prescribed neoadjuvant chemotherapy to test if DHA supplementation enhances chemotherapy efficacy. The DHA supplementation group will take 4.4 g/day DHA orally, and the placebo group will take an equal fat supplement of vegetable oil. The primary outcome will be change in Ki67 labelling index from prechemotherapy core needle biopsy to definitive surgical specimen. The secondary endpoints include assessment of (1) DHA plasma phospholipid content; (2) systemic immune cell types, plasma cytokines and inflammatory markers; (3) tumour markers for apoptosis and tumour infiltrating lymphocytes; (4) rate of pCR in breast and in axillary nodes; (5) frequency of grade 3 and 4 chemotherapy-associated toxicities; and (6) patient-perceived quality of life. The trial has 81% power to detect a significant between-group difference in Ki67 index with a two-sided t-test of less than 0.0497, and accounts for 10% dropout rate. Ethics and dissemination: This study has full approval from the Health Research Ethics Board of Alberta - Cancer Committee (Protocol #: HREBA.CC-18-0381). We expect to present the findings of this study to the scientific community in peer-reviewed journals and at conferences. The results of this study will provide evidence for supplementing with DHA during neoadjuvant chemotherapy treatment for breast cancer. Trial registration number: NCT03831178